Efficacy and Safety of Transarterial Radioembolization in Elderly Patients with Hepatocellular Carcinoma: A Single-Center Experience - Karaoğullarından, Ümit; Gümürdülü, Yüksel; Üsküdar, Oğuz; Odabaş, Emre; Güler, Hasan Selim; Geçkalan, Cansu; Benli, Burcu Arslan; Delik, Anıl; Özdemir, Asena Ayça; Kuran, Sedef (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Hepatocellular carcinoma is a major cause of mortality and morbidity in both cirrhotic and non-cirrhotic patients, and most patients are suitable for locoregional and/or systemic therapy at the time of diagnosis. In this study, we aimed to determine the efficacy and safety of transarterial radioembolization in elderly patients. Materials and Methods: Patients diagnosed with hepatocellular carcinoma between 2013 and 2022 were screened retrospectively. The patients were divided into 2 groups: the elderly (age greater-than or equal to70 years) and the young (age <70 years). Transarterial radioembolization response was evaluated according to the Response Evaluation Criteria in Solid Tumors. Results: Ninety patients were included in the young group, and 56 patients were in the elderly group. It was observed that male dominance was less in the elderly group (P .05). Hepatitis B was the most common cause in both groups. There were no significant differences between groups with regard to morphological features of tumors [tumor focality (single; 62.2% and 60.7%, respectively) and maximal tumor diameter (6.9 and 6.55 cm, respectively)], transarterial radioembolization responses (51.1% and 39.3%, respectively), survival (9 and 8.5 months), and both early and late side effects (P .05). Age was not found to be an effective factor in transarterial radioembolization response (P .05). Conclusion: No differences in the safety and efficacy of transarterial radioembolization were observed between the groups. In addition, it was observed that age was not a predictive factor for adverse events. In elderly patients in the frail group, it should be considered that age alone should not be seen as a limitation in the transarterial radioembolization decision. Cite this article as: Karaoğullarından , Gmrdl Y, skdar O, et al. Efficacy and safety of transarterial radioembolization in elderly patients with hepatocellular carcinoma: A single-center experience. Turk J Gastroenterol. 2024;35(3):204-211.